American Society of Plastic Surgeons Evidence-Based Clinical Practice Guideline Revision: Reduction Mammaplasty. Issue 3 (March 2022) - Perdikis, Galen; Dillingham, Claire; Boukovalas, Stefanos; Ogunleye, Adeyemi A.; Casambre, Francisco; Dal Cin, Arianna; Davidson, Caryn; Davies, Claire C.; Donnelly, Katelyn C.; Fischer, John P.; Johnson, Debra J.; Labow, Brian I.; et al.
Abstract : Summary: A multidisciplinary work group involving stakeholders from various backgrounds and societies convened to revise the guideline for reduction mammaplasty. The goal was to develop evidence-based patient care recommendations using the new American Society of Plastic Surgeons guideline methodology. The work group prioritized reviewing the evidence around the need for surgery as first-line treatment, regardless of resection weight or volume. Other factors evaluated included the need for drains, the need for postoperative oral antibiotics, risk factors that increase complications, a comparison in outcomes between the two most popular techniques (inferior and superomedial), the impact of local anesthetic on narcotic use and other nonnarcotic pain management strategies, the use of epinephrine, and the need for specimen pathology. A systematic literature review was performed, and an established appraisal process was used to rate the quality of relevant scientific research (Grading of Recommendations Assessment, Development and Evaluation methodology). Evidence-based recommendations were made and strength was determined based on the level of evidence and the assessment of benefits and harms.